PENGEMBANGAN MEDIA PEMBELAJARAN BOARD GAME MATERI STRUKTUR DAN FUNGSI TUMBUHAN UNTUK SISWA TINGKAT MENENGAH PERTAMA - Aldya, Riantina Fitra; Umbu, Alce Bili Samuel; Istikomayanti, Yuswa; Pantiwati, Yuni (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This research aims to determine the validity of developing learning media in the form of board games on the structure and function of plant tissue, using ADDIE model development research which will be validated by media experts, material experts, teachers and 20 class VIII students of SMP Negeri 16 Malang. The data collection technique used a questionnaire to test the appearance, material, and ease of use of the board game learning media being developed. The results of the research showed that at the analysis stage there were still some students who had not actively participated independently, so a design was carried out to develop a board game by adapting the components of the Ministry of National Education (2008), followed by media development where the validation results from media experts, material experts and teachers showed the average scores were 4.84, 4.91, and 4.75 in the valid category, while the test results from students showed a result of 4.82 in the feasible category. This is because the board game contains pictures that match the material and are able to increase student activity through active participation of students in the game.